UJI EFEKTIFITAS MINYAK SERAI WANGI (Andropogon nordus L.) TERHADAP KUTU DAUN (Aphis gossypii G.) (HOMOPTERA: APHIDIDAE) - Sasmita, Linda - (Pendidikan Biologi, 2014)
Aphis Gossypii is bad animals that eat some plants. Aphis Gossypiitakes and eats leaf and epidermis structure. Brown leaf and curly is cause by Aphis Gossypii and plant can dead. Take care of plant uses sintetic pepticida that give negative effect toward field. To least using sintetic pepticida need to do improving good field such as, using nabati pepticida and serai wangi oil. Serai wangi oil has citronella unsure that is dangerous contact causing Aphis Gossypii lost energy until dead. The purpose of research is to determine effective serai wangi oil concentration to handle Aphis Gossypii. This research is done from February-March 2014 at Laboratory Zoology College of Teacher Trainning Biology Education STKIP PGRI Sumatera Barat using RAL with 6 treatment and 5 test. As A treatment (bad animals), B (0.1% serai wangi oil), C (0.2% serai wangi oil), D (0.3% serai wangi oil), E (0.4%serai wangi oil), F (0.5% serai wangi oil). Parameter that is researched first dead and mortalitas nimfa Aphis Gossypii.The result of research is analyzed with many diagnoses and BNT test in 5% level. The result of research show that using serai wangi oil giving effect toward first dead mortalitas nimfa Aphis Gossypii. The test result of BNT can be that svery treatment giving value that give different toward first dead mortalitas nimfa Aphis Gossypii. Effective concentration to develop and take care Aphis Gossypii that has 0.4% concentration.